Annex 3: Roles of global and regional networks and consortia in strengthening forestry research - Dykstra, D.P.; Koné, I.; Nair, C.T.S. (1998)
Collaborative institutional arrangements such as networks and consortia are becoming significant in the provision of goods and services in situations where such collaborations can improve the overall comparative advantage of the alliance. Economic globalisation, rapid development of communication technologies and increasing problem complexity have enhanced the relevance of these networks. While networks and strategic alliances are playing an increasingly important role in national and international agricultural research they have been less widely used in forestry for collaborative research. Forestry research networks foster the exchange of information among scientists and to a lesser extent, users and beneficiaries of forestry research. Recent developments in forestry suggest that by broadening the scope of their activities, these networks could contribute much more to forestry research. Many research problems could be handled more effectively through networking than by individual research institutes. In this paper a selection of issues relating to collaboration in forestry research through networks and consortia at the regional and global levels is examined. It is not a comprehensive overview of the subject but rather an attempt to catalogue the many existing forestry research networks and collaborative arrangements. The aim is to raise issues for discussion.